Development of a Disablitiy-Friendly an Inclusive in Sebelas Maret University Library - Masriyatun, Masriyatun; Perwitosari, Henny; Demartoto, Argyo (Edulib, 2021)
Higher education libraries generally provide library material collection needs for non-disabled users, while disabled users also need the same. The purpose of this study was to determine the policy governance of the development of the UPT library at Sebelas Maret University, Surakarta, which was friendly and inclusive, and student responses to the policy governance of the development of the UPT library at Sebelas Maret University, Surakarta, which was pleasant and inclusive. The research method uses qualitative and quantitative descriptive involving 33 respondents. Researchers used questionnaires and interviews to obtain data. The results of this study indicate that the management of library UPT development policies includes information resource management policies, collection development for disabled users, and facilities and infrastructure policies for disabled users. The results of student responses to information resource management policies are high, 63.6%, responses to collection development policies are medium, 36.4%, and answers to facilities and infrastructure development policies are very low, 54.5%. Overall, the student response to the policy of developing the UPT library at Sebelas Maret University, Surakarta, which is disability-friendly and inclusive, is shallow, at 39.4%. The conclusion from these results is that the development of the Disabled and Inclusive UNS Library UPT is essential for improvement, especially policies in the field of facilities and infrastructure.